Chatter-free and equivalent estimator fuzzy model-based sliding mode controller for serial links 6 dof robot manipulator - Yadegar, Sanaz (2015)
Design of a robust controller for multi input-multi output (MIMO) nonlinear uncertain dynamical system could be a challenging work. This thesis focuses on the design and analysis of a high performance Proportional-Integral-Derivative (PID)-like fuzzy sliding mode control for second order nonlinear uncertain system, in presence of uncertainties. In this research, sliding mode controller is a robust and stable nonlinear controller, which selected to control of robot manipulator. The proposed approach effectively combines of design methods from switching sliding mode controller, adaptive controller, fuzzy logic theory and linear Proportional-Derivative (PD) control to improve the performance,stability and robustness of the sliding mode controller. This sliding mode controller has two important subparts, switching and equivalent. Switching part (discontinuous part) is very important in uncertain condition but it causes chattering phenomenon. To solve the chattering, the most common method used is linear boundary layer saturation method, but this method lost the stability. To reduce the chattering with respect to stability and robustness; linear controller is added to the switching part of the sliding mode controller. The linear controller is to reduce the role of sliding surface slope and switching (sign) function. The nonlinearity term of the sliding mode controller is used to eliminate the decoupling and nonlinear term of link’s dynamic parameters. However nonlinearity term of sliding mode controller is very essential to reliability but in uncertain condition or highly nonlinear dynamic systems it can cause some problems. To solve this challenge the PID fuzzy logic controller is used as a modelbased PID like fuzzy sliding mode controller. The PID like fuzzy sliding mode controller is updated based on online tuning sliding surface slope. In order to reduce the online computation burden, the PID like fuzzy logic controller is also used to sliding surface slope online tuning. As a result, in proposed method fuzzy logic controller is used to dynamic estimation and also online tuning. This controller improves the stability and robustness, reduces the chattering as well and reduces the level of energy due to the torque performance as well.